Model Dialog Agama dan Sains dalam Pembelajaran Al-Qur’an Digital: Studi atas Aplikasi Ngaji.ai dalam Perspektif Ian G. Barbour - Muhammad Ubaidilah; Achmad Khudori Soleh (An Natiq, 2026)
Artificial Intelligence (AI) has brought significant changes to human life while simultaneously raising ethical and existential concerns. This article discusses the importance of establishing a dialogue between religion and science in responding to contemporary technological challenges, with reference to the thoughts of Ian G. Barbour. This study aims to examine the relevance of Barbour’s dialogical model as a critical approach in responding to digital Qur’anic learning applications. The method used is qualitative-descriptive with content and interpretative analysis of primary sources from Barbour’s works and the Ngaji.ai application. The findings show that: (1) the four models of the relationship between science and religion proposed by Ian G. Barbour (conflict, independence, dialogue, and integration) offer a framework for aligning scientific rationality with religious wisdom, enabling the construction of a civilization that is not only materially advanced but also meaningful and sustainable for the future of humanity; (2) Qur’anic learning through the Ngaji.ai application promotes a constructive dialogue between science and religion. Through open discussion, AI technology presents a voice-based evaluation system developed by AI experts and curated by professional Qur’an memorizers with expertise in tajwid; and (3) the development process of the Ngaji.ai application reflects a dialogical relationship between religion and science by encouraging mutual engagement, clarification, and respect for each other’s authority. This dialogical model can serve as a foundation to foster an appreciative attitude toward the contributions of science in providing efficiency and accessibility, while maintaining caution to preserve the authenticity of the Qur’anic text and meaning.